Human Resource Management in Schools: Challenges and Strategies in the Digital Age - Lingga Karunia Ilahi; Albi Baehaqi; Agung Ruslan; Pepen Supendi (Beginner: Journal of Teaching and Education Management, 2025)
Human Resource Management (HRM) in schools is a crucial element in advancing the quality of education. In the era of digital transformation, human resource management faces new challenges, particularly related to the adaptation of technology in the learning and administrative processes. This research discusses HRM in schools with a focus on the application of digital technology in managing educational and administrative staff. Digitalization brings significant changes in the ways recruitment, training, and performance management are conducted, by utilizing technology-based management systems such as Human Resource Information Systems (HRIS) and Learning Management Systems (LMS). However, challenges such as resistance to change, digital competence gaps, limited infrastructure, and lack of policy support become obstacles in the implementation of digital transformation in schools. Therefore, strategies such as developing digital competence for educators, implementing technology-based systems, and strengthening digital policies and infrastructure are necessary for effective digitalization in schools. The implementation of these strategies is expected to enhance the efficiency and effectiveness of HRM and improve the quality of education in the digital era.